Modeling of Accounting Information Systems in Companies Implementing the Sharing Economy Business Model - Shintiya Yulia Frantika; Kurnia Ekasari; Aang Afandi (Indonesian Journal of Business Analytics, 2023)
The purpose of this study is to offer modeling of the Accounting Information System, especially the payroll system, using the concept of the Business Process Management System. The object of this research is the online media company PT Kreasi Ngalam Media (AboutMalang.com). Currently, the system that is being used to manage employee data, calculate salaries, and generate reports still relies on manual processes. The use of a web-based employee payroll information system application is expected to provide significant assistance to companies in managing employee data, calculating salaries, and preparing reports. The research method used is qualitative, and the data collection uses primary data sources in the form of direct observation and secondary data sources from the company's payroll reports. The results of this research are in the form of a business process model based on the Business Process Model Notation (BPMN), which can improve effectiveness and efficiency, with an impact on improving the quality of the company's business processes.